Sexual dysfunction in patients with depression presenting in a tertiary care center: a cross-sectional study - Kafle, B; Bagale, Y; Tiwari, S; Pokharel, A (Devdaha Medical Journal, 2026)
Introduction: Sexual dysfunction (SD) is common in depression, with prevalence ranging from 46.6% to 90%. In Nepal, there has been no research on sexual dysfunction in depression,especially among males. This study aimed to determine the prevalence of sexual dysfunction among Nepalese patients with a first episode of major depression. Methods: A hospital-based cross-sectional study was conducted in the Department of Psychiatry, Devdaha Medical College, from 15th January 2025 to 15th July 2025. Patients diagnosed with depression were selected using purposive sampling. The Arizona Sexual Experience Scale (ASEX) was utilized to evaluate sexual dysfunction. Ethical approval was obtained from the Institutional Review Committee (Reference No: 18/2024), and informed consent was secured from all participants prior to data collection. Data entry and analysis were performed using the Statistical Package for the Social Sciences (SPSS) version 24.0. Point estimates with 95% confidence intervals were calculated. Binary variables were summarized using frequencies and percentages, while continuous variables were presented as mean and standard deviation. Results: Among 280 participants, sexual dysfunction was present in158 (56.4%). The median age was 36 years, and most of them had moderate depression 216 (77%). Sexual dysfunction was slightly more prevalent in males (57.0%) than in females (43.0%). The mean ASEX score was 17.39 ± 4.46, higher in males. The most common issue was decreased sexual desire in both genders, followed by erection difficulties in males and lubrication problems in females. Conclusion: Sexual dysfunction was common among patients with depression, with slightly higher rates in males. Routine and sensitive assessment of sexual functioning should be part of psychiatric evaluation, as early identification allows timely management and helps improve treatment outcomes and quality of life.